1931
DOI: 10.1104/pp.6.3.485
|View full text |Cite
|
Sign up to set email alerts
|

Water-Supplying Power of the Soil Under Different Species of Grass and With Different Rates of Water Application

Abstract: The water-supplying power of the soil has been investigated by a num-,ber of workers during the past 30 years. The soil-point method which is used in this study was described by LIVINGSTON and KOKETSU (3). This method has since been used to study the seasonal variations in the watersupplying power of the soil with reference to rainfall, evaporation rate and the growth condition of lawn grasses by LIVINGSTON and OHGA (4) Only four of the seven plots were used in the study reported here. These included one chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1932
1932
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In contrast, P. trivialis, located on an adjacent plat, has had to be reseeded annually, since it has died out each season within the space of a few weeks after the inieeption of hot, dry weather. In a study of the water-supplying power of soil under different gorasses, WELTON anid WILSON (29) found that fescues apparently absorb less of the available soil moisture than do bluegrass and benits, and WILSON and LIVINGSTON (31) ill a study of the wilting of grasses as related to the water-suipplying power of the soil found the fescues to be more drought-resistant than the other species tested.…”
Section: Soil Droughtmentioning
confidence: 99%
“…In contrast, P. trivialis, located on an adjacent plat, has had to be reseeded annually, since it has died out each season within the space of a few weeks after the inieeption of hot, dry weather. In a study of the water-supplying power of soil under different gorasses, WELTON anid WILSON (29) found that fescues apparently absorb less of the available soil moisture than do bluegrass and benits, and WILSON and LIVINGSTON (31) ill a study of the wilting of grasses as related to the water-suipplying power of the soil found the fescues to be more drought-resistant than the other species tested.…”
Section: Soil Droughtmentioning
confidence: 99%
“…and Wilson(7) found 60% more available water under Chewings red fescue than under l(entucky bluegrass. He concluded that the fescue places smaller demands on available moisture and thus enters drouth with greater reserve moisture.…”
mentioning
confidence: 93%
“…The idea already advanced by LIVINGSTON (31), that the water-supplying-power value of about 100 (for the 6-cm. depth) may be regarded as critical for many plants and for ordinary evaporation condi--I't 27 and 29 respectively, but the experimental period was not prolonged sufficiently to bring about complete vegetative death in these two forms.…”
Section: Introductionmentioning
confidence: 99%